Research on dehumidification optimization of steam turbine wet steam stage hollow stator cascade heating - Xu Han; Jiandong Guan; Qiuliang Zhu; Zhengqi Chen; Bochuan Yao; Wensheng Zhao; Zhonghe Han (Case Studies in Thermal Engineering, 2023)
The secondary water droplets in the steam turbine wet steam stage are easy to cause water erosion damage to the rotor cascade, and there is a large speed slip between the main steam flow and the secondary water droplets, which will seriously affect the safe and stable operation and reduce the efficiency of the steam turbine. Secondary water droplets are formed when the water film deposited on the stator blade surface falls off at the trailing edge. Therefore, controlling the formation of a water film on the stator blade surface plays an important role in improving the efficiency and safety of the steam turbine wet steam stage. Based on the current research situation at home and abroad, taking the Dykas cascade as the research object, it is found that the covering area of dry steam film on blade surface expands with the increase of temperature and flow of hot steam inlet. With the increase of hot steam back-pressure, the wetness of blade surface increases. When the average heat flux on the blade surface reaches 5000W/m2, there will be no water film falling off the blade surface. By orthogonal test, the expression between the average heat flux on the blade surface, the inlet temperature, the flow rate and the back-pressure was obtained. The research results can provide reference for the parameter design of steam turbine hollow stator heating dehumidification.